2015
DOI: 10.1152/ajpheart.00043.2015
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyocyte mitochondrial respiration is reduced by receptor for advanced glycation end-product signaling in a ceramide-dependent manner

Abstract: Cigarette smoke exposure is associated with an increased risk of cardiovascular complications. The role of advanced glycation end products (AGEs) is already well established in numerous comorbidities, including cardiomyopathy. Given the role of AGEs and their receptor, RAGE, in activating inflammatory pathways, we sought to determine whether ceramides could be a mediator of RAGE-induced altered heart mitochondrial function. Using an in vitro model, we treated H9C2 cardiomyocytes with the AGE carboxy-methyllysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 46 publications
(54 reference statements)
3
35
0
Order By: Relevance
“…Ray et al showed MGO inhibits electron flow through complex I leading to mitochondrial dysfunction [33, 34]. In addition, some reports revealed that AGEs can also trigger mitochondrial dysfunction [35, 36]. These studies provide a strong support for our study about MGO-induced mitochondrial dysfunction.…”
Section: Discussionsupporting
confidence: 77%
“…Ray et al showed MGO inhibits electron flow through complex I leading to mitochondrial dysfunction [33, 34]. In addition, some reports revealed that AGEs can also trigger mitochondrial dysfunction [35, 36]. These studies provide a strong support for our study about MGO-induced mitochondrial dysfunction.…”
Section: Discussionsupporting
confidence: 77%
“…Moreover, AGEs have been shown to induce the expression of ENaC via activation of SGK1 [57]. Recent evidence in mice suggests there is RAGE upregulation in cardiomyocytes that contributes to cardiomyopathy [58]. Herein, we show that myocardial AGE expression is increased in DbC and DbE, compared to CkC, and observe that it is widely distributed throughout the LV wall, including in the vasculature.…”
Section: Discussionmentioning
confidence: 60%
“…An underlying mechanistic theme of the smoke-related disease states outlined in this review is chronic inflammation, in which RAGE is a key modulator. Essential to understanding the clear link between RAGE and disease progression is the key concept that RAGE expression is increased by exposure to tobacco smoke [5,209,210,211,212] and the induction of RAGE causes inflammatory disease symptoms similar or identical to the ones described herein [23,195,213,214,215,216,217]. …”
Section: Rage: a Plausible Unifying Mechanismmentioning
confidence: 95%
“…Of note, RAGE is most abundantly expressed in the lung, the tissue in which it was initially discovered. Although RAGE is predominantly expressed in the lung, it is detectable in a variety of tissues including the heart, brain, placenta, liver, kidney, pancreas, small intestine, and colon [4,5]. RAGE is a pattern recognition cell surface receptor that binds many endogenous and exogenous entities such as S100/calgranulins [218], amyloid-β-peptide [219], HMGB-1 [220], and AGEs [221].…”
Section: Rage: a Plausible Unifying Mechanismmentioning
confidence: 99%
See 1 more Smart Citation